HNF1 alpha gene coding regions mutations screening, in a Caucasian population clinically characterized as MODY from Argentina - Lopez, Ariel Pablo; Foscaldi, Sabrina Andrea; Perez, Maria Silvia; Rodriguez, Martín; Traversa, Mercedes; Puchulu, Félix Miguel; Bergada, Ignacio; Frechtel, Gustavo Daniel (Diabetes research and clinical practice, 2011)
There are at least six subtypes of Maturity Onset Diabetes of the Young (MODY) with distinctive genetic causes. MODY 3 is caused by mutations in HNF1A gene, an insulin transcription factor, so mutations in this gene are associated with impaired insulin secretion. MODY 3 prevalence differs according to the population analyzed, but it is one of the most frequent subtypes. Therefore, our aims in this work were to find mutations present in the HNF1A gene and provide information on their prevalence. Mutations screening was done in a group of 80 unrelated patients (average age 17.1 years) selected by clinical characterization of MODY, by SSCP electrophoresis followed by sequenciation. We found eight mutations, of which six were novel and four sequence variants, which were all novel. Therefore the prevalence of MODY 3 in this group was 10%. Compared clinical data between the non-MODY 3 patients and the MODY 3 diagnosed patients did not show any significant difference. Eight patients were diagnosed as MODY 3 and new data about the prevalence of that subtype is provided. Our results contribute to reveal novel mutations, providing new data about the prevalence of that subtype.